Simple synthetic methods towards reactive low valent germanium compounds - Muhammad Luthfi Ismail (2019)
This thesis describes the unique synthetic strategy towards a variety of low oxidation state germanium compounds without the use of harsh reagents. Chapter 1 describes the synthesis of a phosphine-stabilized phosphidogermanium(I) dimeric derivative, [Ge(Cl){N(Ar)PPh2}(Ph2P)Ge:]2 (1.3) isolated from a reaction of [L{(Ar)(Ph2P)N}Si:] (1.1) and GeCl2.dioxane. Compound 1.3 was isolated alongside the amidinato amidosilylene – germylene adduct, [L{(Ar)(Ph2P)N}Si:GeCl2] (1.2). A crude 29Si NMR spectrum of the mother liquor revealed the presence of silaamine [LSi(=NAr)Cl] (1.4) and trichlorosilane derivative (LSiCl3) (1.5). The thermal conversion of 1.1 to its constitutional isomer, together with the isolated products, and detected intermediates hints at a possible mechanism which involves several redox processes. Additionally, the preliminary reactivity of compound 1.3 with B(C6F5)3 resulted in the formation of its oxidised product [{Ph2PN(Ar)GeCl}{Ph2PGeCl}] (1.7). Chapter 2 describes the isolation of a variety of transition metallogermylene complexes by a reaction of base – stabilized germanium(I) dimer [LGe:]2 (2.1, L = 2-imino-5,6-methylenedioxylphenyl) with various transition metal complexes. These reactions represent a rare example of metallogermylene synthesis without the use of harsh transition metallate complexes in salt metathesis reactions. Chapter 3 describes the simple synthesis of the first germylenylsilylene (3.3) starting from the 2-imino-5,6-methylenedioxylphenylchlorogermylene (3.1). Suitable crystals of compound 3.3 for X-ray crystallography could not be isolated due to its inherent instability. Compound 3.3 decomposes into unidentified products within days in solution. However, it is sufficiently stable to be characterized by multinuclear NMR spectroscopy. An in-situ generated 3.3 can undergo a clean reaction with 2 equivalents of 2,6-diisopropylphenylazide at low temperature to form compound 3.4. Compound 3.4 represents a rare example of a silaamidinato germylene. The proposed structure of compound 3.3 can be inferred from the molecular structure of 3.4.